Clinical and molecular characteristics of 1qter microdeletion syndrome: delineating a critical region for corpus callosum agenesis/hypogenesis. Issue 6 (4th January 2008) - van Bon, B W M; Koolen, D A; Borgatti, R; Magee, A; Garcia-Minaur, S; Rooms, L; Reardon, W; Zollino, M; Bonaglia, M C; De Gregori, M; Novara, F; Grasso, R; et al.
Abstract : Background: Patients with a microscopically visible deletion of the distal part of the long arm of chromosome 1 have a recognisable phenotype, including mental retardation, microcephaly, growth retardation, a distinct facial appearance and various midline defects including corpus callosum abnormalities, cardiac, gastro-oesophageal and urogenital defects, as well as various central nervous system anomalies. Patients with a submicroscopic, subtelomeric 1qter deletion have a similar phenotype, suggesting that the main phenotype of these patients is caused by haploinsufficiency of genes in this region. Objective: To describe the clinical presentation of 13 new patients with a submicroscopic deletion of 1q43q44, of which nine were interstitial, and to report on the molecular characterisation of the deletion size. Results and conclusions: The clinical presentation of these patients has clear similarities with previously reported cases with a terminal 1q deletion. Corpus callosum abnormalities were present in 10 of our patients. The AKT3 gene has been reported as an important candidate gene causing this abnormality. However, through detailed molecular analysis of the deletion sizes in our patient cohort, we were able to delineate the critical region for corpus callosum abnormalities to a 360 kb genomic segment which contains four possible candidate genes, but excluding the AKT3 gene.